The Quality of Perceived Parenting and Its Association with Peer Relationships and Psychological Distress in a Group of Incarcerated Young Offenders - Chambers, Julie A. (International journal of offender therapy and comparative criminology, 2000)
An investigation was carried out to examine the association of perceived parenting as measured by a shortened form of the Parental Bonding Instrument with self-esteem, relationships with peers and staff, and psychological distress levels in a group of young offenders held in custody. There were strong associations between low parental care with both low self-esteem and increased psychological distress as well as between low maternal care and poorer peer relationships. In addition, poor-quality peer relationships with other inmates and low self-esteem showed strong associations with increased levels of psychological distress in prison, suggesting that peer relations and self-esteem may both act as mediator variables in the association between parental care and anxiety and depression. There were, however, no associations between self-esteem and either the quality or number of peer relationships